2007 9th International Symposium on Signal Processing and Its Applications 2007
DOI: 10.1109/isspa.2007.4555604
|View full text |Cite
|
Sign up to set email alerts
|

Volterra-Laguerre modeling for NMPC

Abstract: Volterra series are perhaps the best understood nonlinear system representations in signal processing. They can be used to model a wide class of nonlinear systems. However, since these models are non-parsimonious in parameters, the symmetric kernel parameters are used. This model is used to evaluate identification of a pH-neutralization process. The aim is to use this model in nonlinear model predictive control framework. For this purpose various orders of the Laguerre filters and also Volterra kernels are tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The Laguerre Polynomials are a series of orthogonal polynomials that can be used to reduce the number of coefficients required to describe a Volterra kernel. The application of orthogonal functions to identification and control is not new, see (Schetzen, 1980), (Dumont et al, 1991), Zafiriou, 1994), (Mäkila, 1990), (Clement, 1982), (Mahmoodi et al, 2007), (Zheng and Zafiriou, 1995),and (Lee, 1960). A mathematical review of orthogonal and orthonormal fucntions can be found in Appendix 6.…”
Section: The Laguerre Polynomialsmentioning
confidence: 99%
“…The Laguerre Polynomials are a series of orthogonal polynomials that can be used to reduce the number of coefficients required to describe a Volterra kernel. The application of orthogonal functions to identification and control is not new, see (Schetzen, 1980), (Dumont et al, 1991), Zafiriou, 1994), (Mäkila, 1990), (Clement, 1982), (Mahmoodi et al, 2007), (Zheng and Zafiriou, 1995),and (Lee, 1960). A mathematical review of orthogonal and orthonormal fucntions can be found in Appendix 6.…”
Section: The Laguerre Polynomialsmentioning
confidence: 99%
“…Over the years, numerous nonlinear empirical models have been reported in literature, e.g. Volterra models (Ljung 2010;Mahmoodi 2007), artificial neural networks (Norgaard 2000), fuzzy-logic based models (Beyhan & Alci 2010), nonlinear auto regressive with exogenous input (NARX) models (Nelles 2001), some combinations of them like neuro-fuzzy models (Babuška & Verbruggen 2003), support vector machine and kernel methods of modeling (Tötterman & Toivonen 2009) and wavelet decomposition based methods (Billings 2005). One modeling technique that has been gaining popularity in the recent past is the support vector machine (SVM) (Suganyadevi & Babulal 2014;Tötterman & Toivonen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, task patterns in nuclear reactor operational environment requires reliable control algorithms which will be able to provide an estimation that maintains predictive power both in mild, high speed and difficult tasks carried out by the manipulator. This necessitates development of more sophisticated and high performance identification [7,15,16,22,23,24] and model-based control algorithms working based on a reliable dynamic model of the manipulator. Therefore, developing a more general nonlinear dynamic model of the bespoke robot which has the potential to be utilized for design and development of such a model-based nonlinear control strategies determines the major motivation of this paper.…”
mentioning
confidence: 99%